Design Optimization and Performance Enhancement of Small-Scale Vortex-Induced Turbines for Sustainable Energy Generation - Sheikh Hassan, Sheikh Alif Habibullah; Mohd, Sofian (Progress in Aerospace and Aviation Technology, 2025)
This study presents the development and evaluation of a vortex bladeless wind turbine prototype designed to harness wind energy in low wind speed conditions, making it suitable for regions such as Malaysia. The prototype consists of a 2-meter-tall, 0.2-meter-diameter cylindrical structure mounted on a flexible shaft, which utilizes vortex-induced vibrations to generate mechanical energy. Testing was conducted in a wind tunnel with airflow ranging from 1 m/s to 10 m/s, as well as in outdoor field locations around UTHM. Results demonstrated the turbine’s effectiveness at low to moderate wind speeds. Vibrations were converted into electrical energy using an electromagnetic induction system. Analysis of oscillation frequency, voltage output, and efficiency indicated promising performance under conditions where traditional turbines are less effective. Design enhancements further improved the turbine’s performance.